2021
DOI: 10.1021/acsnano.1c07048
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity Dictates Spontaneous Helix Formation of Thermoresponsive Colloidal Chains in Poor Solvent

Abstract: The formation of helical motifs typically requires specific directional interactions. Here, we demonstrate that isotropic interparticle attraction can drive self-assembly of colloidal chains into thermo-reversible helices, for chains with a critical level of backbone rigidity. We prepare thermoresponsive colloidal chains by cross-linking PNIPAM microgel-coated polystyrene colloids (“monomers”), aligned in an AC electric field. We control the chain rigidity by varying cross-linking time. Above the LCST of PNIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…where u i is the unit vector of U i = r i × r i+1 . A simple uncharged, semi-flexible polymer chain shows H2 values ≈ 0 (or negative values of H2) as expected for a chain locally bent due to thermal fluctuations, while calculating H2 over helical segments of a polymer chain would lead to high positive values of H2 [14,34].…”
Section: A Helix Formationmentioning
confidence: 68%
See 2 more Smart Citations
“…where u i is the unit vector of U i = r i × r i+1 . A simple uncharged, semi-flexible polymer chain shows H2 values ≈ 0 (or negative values of H2) as expected for a chain locally bent due to thermal fluctuations, while calculating H2 over helical segments of a polymer chain would lead to high positive values of H2 [14,34].…”
Section: A Helix Formationmentioning
confidence: 68%
“…Thus, the helical structure is ubiquitous in the macro-molecular world. This has spurred a number of studies that investigate their emergence in several natural systems [4,[6][7][8][9][10][11][12][13][14][15]. Furthermore, helical motifs in synthetic molecules have been explored for their key technological ramifications [16] such as the synthesis of NEMs devices [17][18][19][20][21][22], piezoelectric devices [23] and other optical materials [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 The strain computed from the approximated elastic energy of such deformations helps us to distinguish their predominant driving mechanism by considering the possible causes, such as screw dislocations, thermal/mechanic/compositional fields, and heteromeric stress. 3 Organic chiral molecules can be assembled into twisted arrangements in one direction by symmetry breaking, 4 and chiral additives can further enhance the chiral expression in the form of helixes and/or preferably handedness, even in achiral systems. 5 The surface charge ultimately accumulated from electrostatics and piezoelectricity is, in a few specific instances, another way to create a twisted arrangement in a material.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to molecular subunits within polymers, colloidal particles can also be used as the self-repeating monomeric precursors, linking into 1D colloidal chains. To achieve this, various strategies have been proposed for the fabrication of colloidal chains with distinct architectures, lengths, and compositions including chemical bonding, , electrostatic interactions, ,, hydrogen bonding, directional interaction patches, ,, coordination chemistry, heat, optical traps, UV light, and external fields. ,, We have recently demonstrated the fabrication of chains that were chemically linked from beads assembled under a 1D magnetic field and have also shown that these colloidal chains can be actuated via different mechanisms upon magnetic field application. , …”
Section: Introductionmentioning
confidence: 99%